The Role of Payakumbuh 4 Vocational School Teachers in Managing School Information Media Through Citizen Journalism - Oktri Permata Lani; Refika Mastanora; Zafirah Quroatun 'Uyun; Benni Handayani (Fakultas Usluhuddin dan Dakwah UIN Syekh Wasil Kediri, 2024)
The use of technology and the internet has also had a big impact on the field of education, especially in the daily learning process. The increasingly sophisticated development of technology today means that teachers and students can search for materials and teaching materials from anywhere, at any time, and from anyone. Education today tends to be flexible, more open, and easily accessible to anyone who needs it regardless of status, position or profession, a person's gender status, be it male or female, a person's age, whether a child, old person, teenager, or person. Adults, or educational experiences, and will continue to grow in the form of online learning systems. One of them is that school information media is used as a learning medium to hone teachers' skills, especially in writing. Teachers can apply citizen journalism. In this research, the researcher focused on two objectives, namely, The Role of Teacher Writing in the Citizen Journalism Process for managing school information media and The Role of Teacher Writing in the Citizen Journalism Process for managing school information media. The research method used is a descriptive qualitative approach. The results of this research illustrate the role of SMKN 4 Payakumbuh teachers in managing school information media through citizen journalism, which is not just information but also a medium for learning and honing skills for teachers.